Current status of health systems financing and oversight for end-stage kidney disease care: a cross-sectional global survey. Issue 7 (9th July 2021) - Yeung, Emily; Bello, AK; Levin, Adeera; Lunney, Meaghan; Osman, Mohamed A; Ye, Feng; Ashuntantang, Gloria; Bellorin-Font, Ezequiel; Benghanem Gharbi, Mohammed; Davison, Sara; Ghnaimat, Mohammad; Harden, Paul; et al.
Abstract : Objectives: The Global Kidney Health Atlas (GKHA) is a multinational, cross-sectional survey designed to assess the current capacity for kidney care across all world regions. The 2017 GKHA involved 125 countries and identified significant gaps in oversight, funding and infrastructure to support care for patients with kidney disease, especially in lower-middle-income countries. Here, we report results from the survey for the second iteration of the GKHA conducted in 2018, which included specific questions about health financing and oversight of end-stage kidney disease (ESKD) care worldwide. Setting: A cross-sectional global survey. Participants: Key stakeholders from 182 countries were invited to participate. Of those, stakeholders from 160 countries participated and were included. Primary outcomes: Primary outcomes included cost of kidney replacement therapy (KRT), funding for dialysis and transplantation, funding for conservative kidney management, extent of universal health coverage, out-of-pocket costs for KRT, within-country variability in ESKD care delivery and oversight systems for ESKD care. Outcomes were determined from a combination of desk research and input from key stakeholders in participating countries. Results: 160 countries (covering 98% of the world's population) responded to the survey. Economic factors were identified as the top barrier to optimal ESKD care in 99 countries (64%). Full public funding for KRT was more common than for conservative kidney management (43% vs 28%). Among countries that provided at least some public coverage for KRT, 75% covered all citizens. Within-country variation in ESKD care delivery was reported in 40% of countries. Oversight of ESKD care was present in all high-income countries but was absent in 13% of low-income, 3% of lower-middle-income, and 10% of upper-middle-income countries. Conclusion: Significant gaps and variability exist in the public funding and oversight of ESKD care in many countries, particularly for those in low-income and lower-middle-income countries.